Fatigue Performance of Steel-Concrete Composite Continuous Box Girder Bridge Deck. (8th June 2021) - Zheng, Yuanxun; Cao, Zhanlin; Guo, Pan; Gao, Pu; Zhang, Peng
Abstract : The fatigue performance of the bridge deck significantly affects the safety and durability of the overall steel-concrete composite beam bridge. Based on the vehicle flow information of the highway within 10 years, the fatigue performance of a two-way four-lane steel-concrete composite continuous beam bridge deck is studied in this research. The results indicate that the effect of the wheel track position is negligible for two-way four-lane bridge when the wheel track sways laterally, and the fatigue stress of bridge deck concrete is the most unfavorable while the loading position is 7.0 m away from the bridge center line. The fatigue damage decreases by 30%–40% when the centerline of the lane deviates from the most unfavorable stress position by 1 m. The punching fatigue of the concrete is more sensitive to the changes in slab thickness, and the thickness of the deck concrete slab is recommended to be ≥35 cm.